2x+7=6x-14

Simple and best practice solution for 2x+7=6x-14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+7=6x-14 equation:


Simplifying
2x + 7 = 6x + -14

Reorder the terms:
7 + 2x = 6x + -14

Reorder the terms:
7 + 2x = -14 + 6x

Solving
7 + 2x = -14 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
7 + 2x + -6x = -14 + 6x + -6x

Combine like terms: 2x + -6x = -4x
7 + -4x = -14 + 6x + -6x

Combine like terms: 6x + -6x = 0
7 + -4x = -14 + 0
7 + -4x = -14

Add '-7' to each side of the equation.
7 + -7 + -4x = -14 + -7

Combine like terms: 7 + -7 = 0
0 + -4x = -14 + -7
-4x = -14 + -7

Combine like terms: -14 + -7 = -21
-4x = -21

Divide each side by '-4'.
x = 5.25

Simplifying
x = 5.25

See similar equations:

| .5x-2=8 | | 9m-15=66 | | 4(2p-2)=3(2p+4) | | -3(2-1x)=2x-9 | | 2=-2y+6/13 | | 10y=-5x-15 | | 11x=-42 | | 3+log[4](x+6)=4 | | 0.12x^2-0.72x-0.137=0 | | 100x+100x^2-45=0 | | 2014-1952+-7abc+18=62 | | -2(3x-4)=-(2x-2) | | 0.12x^2+-0.72x+-0.137=0 | | 20x-24=2x | | -11=7-1x | | 45g+7=-6 | | x^3-(2x^2)+1.25x-0.25=0 | | 1952-7abc+18=62 | | 2+2k=8k+3-6k | | x^3-(2x^2)+1.5x-0.25=0 | | 5n-8=n+27 | | [9(y+5)-17]-[3(y-4)+3]= | | 5x-3+7x=45 | | 2+2k=8k+3-6 | | 2(x-2)=3x-4x+5 | | 2x+10=6x-4 | | 7-3(3)=-3+1 | | 17.50-8.75= | | (n+4)-(-3n-7)= | | k/15-13=4 | | 7k^2-54k-16= | | [7(z+5)-17]+[3(z-2)+2]= |

Equations solver categories